The forkhead-box family of transcription factors: Key molecular players in colorectal cancer pathogenesis 06 Biological Sciences 0604 Genetics 11 Medical and Health Sciences 1112 Oncology and Carcinogenesis 06 Biological Sciences 0601 Biochemistry and Cell Biology (2019)
Colorectal cancer (CRC) is the third most commonly occurring cancer worldwide and the fourth most frequent cause of death having an oncological origin. It has been found that transcription factors (TF) dysregulation, leading to the significant expression modifications of genes, is a widely distributed phenomenon regarding human malignant neoplasias. These changes are key determinants regarding tumour's behaviour as they contribute to cell differentiation/proliferation, migration and metastasis, as well as resistance to chemotherapeutic agents. The forkhead box (FOX) transcription factor family consists of an evolutionarily conserved group of transcriptional regulators engaged in numerous functions during development and adult life. Their dysfunction has been associated with human diseases. Several FOX gene subgroup transcriptional disturbances, affecting numerous complex molecular cascades, have been linked to a wide range of cancer types highlighting their potential usefulness as molecular biomarkers. At least 14 FOX subgroups have been related to CRC pathogenesis, thereby underlining their role for diagnosis, prognosis and treatment purposes. This manuscript aims to provide, for the first time, a comprehensive review of FOX genes' roles during CRC pathogenesis. The molecular and functional characteristics of most relevant FOX molecules (FOXO, FOXM1, FOXP3) have been described within the context of CRC biology, including their usefulness regarding diagnosis and prognosis. Potential CRC therapeutics (including genome-editing approaches) involving FOX regulation have also been included. Taken together, the information provided here should enable a better understanding of FOX genes' function in CRC pathogenesis for basic science researchers and clinicians. © 2019 The Author(s).